A multi-disciplinary approach to explaining workless-ness in Britain. Issue 7 (10th July 2017) - Cagliesi, Gabriella; Hawkes, Denise Donna; Tookey, Max
Abstract : Purpose: The purpose of this paper is to adopt the principles of labour economics, behavioural economics and social influence to identify constraints and enablers that influence people's choices in relation to the labour market decisions. Design/methodology/approach: A sequential empirical methodology has been adopted, where data from the British Household Panel Survey (2009) has been collected to explain various statuses of labour market activity, with a focus on workless-ness, across the categories of unemployment, being a student, disability, retirement and being a carer – differentiating for gender and age. The paper develops and substantiates the hypothesis theoretically and gives some indications using a multi-disciplinary approach. Findings: The authors found that labour market opportunities, choices and achievements are affected by the interrelations and interactions of an individual's demographic and psychological characteristics (such as age, gender, heuristics, perceptions, beliefs, attitude's goals and ambitions) along with external factors (such as geographical, socio- cultural and economic conditions). Originality/value: This study makes a unique contribution to labour economics as the authors abandon the traditional welfare approach and use a more general framework of capabilities and refined functioning to interpret how different types of constraints – ranging from socio-economic conditions and environmental background to specific features of individual processes of choices and decision making – affect preferences and functioning's. The study also identifies how "under-employment" complements the use of BE/social influence in explaining labour market inactivity, and highlights how the findings of this study have important implications for policy.